TEACHING READING BY USING INQUIRY BASED LEARNING (IBL) SISCA WULANSARI SAPUTRI - Sisca Wulansari Saputri (FKIP, Universitas Banten Jaya, 2018)
The study is aimed to explain the using of Inquiry-based learning for teaching reading at English Department UNBAJA 2016/2017. The researcher got the data of this research from events, informant and document. This research is descriptive qualitative research. The method of collecting data is observation, interview and document. The technique of data analysis is data reduction, data display and conclusion drawing/verification. The result of the analysis show that: 1) For learning objective there are two kinds namely: general learning objective and specific learning objective. 2) In the classroom procedure, the researcher found that the lecture used Inquiry based learning in teaching Reading at Literal Reading Class. Any three steps, there are: Exploration, Elaboration and Confirmation. 3) The classroom technique that the researcher found during the observation such as oral repetition, identifying key-words, answering the questions, free writing, problem solving and reading passage. 4) The researcher found four kinds of Instructional materials during the observations, there are (a) textbook, (b) picture in the monitor, (c) slide of power point, and (d) video. 5) There are two of lectures’ role that the researcher found in the English Department UNBAJA during the observation. 6) media that used in English Department UNBAJA, which is used in teaching learning process at Literal Reading class such as: (a) picture, (b) Board, (c) Laptop, and (d) tape recorder. And 7) Type of Assessment tools used are daily test, midterm examination and final examination. The results showed thatstudents who were instructed through Inquiry-Based Learning (IBL) were achieved higher score than the ones which wereinstructed through the traditional method.